The role of ATP6V0D2 in breast cancer: associations with prognosis, immune characteristics, and TNBC progression - Zhang, Jingyu; Yang, Lixian; Xu, Bin; Ji, Haibo; Liu, Shuo; Wang, Xiaohan; Li, Xiaolong; Wang, Quanle; Song, Zhenchuan (Frontiers in Oncology, 2024)
ObjectiveResearches have identified ATPase H+ transporting V0 subunit d2 (ATP6V0D2) as a significant factor in various cancers. However, its prognostic value in breast cancer (BRCA) and its biological role in BRCA cells remain unclear.MethodsIn this research, we examined the varying expression levels of ATP6V0D2 in both BRCA and normal breast tissue by utilizing information derived from databases including the Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO), along with clinical samples. Survival studies were carried out to investigate the link between ATP6V0D2 levels and prognosis in BRCA patients. A series of enrichment analyses identified possible pathways associated with the differentially expressed genes in BRCA. The relationships among ATP6V0D2 expression, immune characteristics, and gene mutation were evaluated using Spearman’s test. Finally, the expression of ATP6V0D2 was identified by quantitative real-time polymerase chain reaction (RT-qPCR) alongside western blot analysis. Additionally, Cell Counting kit-8 (CCK-8), Colony formation, Transwell, Scratch healing, and Mouse xenograft tumor assays were conducted to assessed the impact of ATP6V0D2 knockdown on the biological functions in TNBC.ResultsATP6V0D2 exhibited high expression in a range of cancers and correlated with unfavorable prognosis in BRCA. Functional enrichment analyses revealed enrichment of extracellular matrix-receptor interaction, focal adhesion, and the signaling pathway of tumor growth factor-beta in the high ATP6V0D2 expression group. Additionally, ATP6V0D2 was closely associated with immune checkpoints. Its expression positively associated with the infiltration levels of macrophage and neutrophil, but inversely with CD8+ T and plasmacytoid dendritic cells. Mutation analysis revealed that PIK3CA, linked to decreased OS, exhibited a higher mutation rate in the ATP6V0D2 high expression group. Furthermore, ATP6V0D2 knockdown inhibited TNBC cells invasion, migration, and proliferation abilities.ConclusionATP6V0D2 acts as a promising indicator for both diagnosis and prediction of outcomes in breast cancer and could potentially be a novel therapeutic target for BRCA.